Hierarchical Cobalt‐Nickel Double Hydroxide Arrays Assembled on Naturally Sedimented Ti3C2Tx for High‐Performance Flexible Supercapacitors. (29th December 2021) - Bai, Zuxue; Zhang, Deyang; Guo, Ying; Yang, Ya; Yan, Hailong; Wang, Yangbo; Cheng, Jinbing; Chu, Paul K.; Pang, Huan; Luo, Yongsong
Abstract: Flexible electrodes with excellent energy storage and conversion properties that can be produced by a simple process are highly desirable for supercapacitors. Herein, Cobalt‐Nickel double hydroxide (CoNi‐DH) micro‐nanosheet arrays are prepared uniformly on naturally sedimented Ti3 C2 Tx films by an etching‐deposition‐growth process to form a CoNi‐DH@Ti3 C2 Tx heterostructure. The naturally sedimented Ti3 C2 Tx film serves as the substrate to minimize aggregation of the CoNi‐DH nanoarrays to enhance the electrical conductivity. Furthermore, the hierarchical structure comprised of the CoNi‐DH interconnected nanoarrays promotes electrolyte access. By taking advantage of the excellent electrical conduction and high theoretical specific capacitance, the flexible CoNi‐DH@Ti3 C2 Tx electrode in the supercapacitor delivers a superior specific capacitance of 919.5 F g −1 at 1 A g −1, and remarkable capacitance retention of 89.6% after 5000 cycles at 20 A g −1 . Density‐functional theory calculations are performed to investigate the charge density difference and partial density of states of CoNi‐DH@Ti3 C2 Tx and the theoretical assessment suggests that the chemical bonds between Ti3 C2 Tx and CoNi‐DH are critical to the charge transport, electrical conductivity, and structural stability. Abstract : Hierarchical CoNi‐DH micro‐nanosheet arrays are prepared uniformly on naturally sedimented Ti3 C2 Tx films by an etching‐deposition‐growth process to form a CoNi‐DH@Ti3 C2 Tx heterostructure. The naturally sedimented Ti3 C2 Tx film serves as the substrate to minimize aggregation of the CoNi‐DH nanoarrays to enhance the electrical conductivity, and the hierarchical structure comprising the CoNi‐DH interconnected nanoarrays promotes electrolyte access.